Characterization of a Phosphate Solubilizing and Pesticide Tolerant Endophytic Bacterium (Pseudomonas sp.) Isolated from Apple Orchards of Himachal Pradesh - Khatri, Shakuntala; Shridhar, Vijay; Pandey, Anita (International Journal of Research Innovation and Entrepreneurship, 2020)
Jammu-Kashmir, Himachal Pradesh and Uttarakhand are the core areas of apple production in India. Synthetic chemicals, fertilizers, and pesticides are used for improving the yield in apple orchards. Overuse of phosphate fertilizers, untreated/ treated wastewater, sewage sludge, composts, etc leads to serious conditions in apple orchards. In the present study, enrichment culture technique was used to isolate and screen the pesticide tolerant bacterial strain from apple roots. A bacterial culture, identified as Pseudomonas sp., was obtained to possess phosphate solubilizing and pesticide tolerance properties. It tolerated Ridomil 80%, Meera 71, carbendazim and sulphur 50% up to 1000 µg/ml. The bacterium also showed tolerance to streptomycin up to 50 µg/ml.